Distributed Practice Learning Model Using Audiovisual Media for Teaching Basic Skills of Badminton - Ilham Kamaruddin; Muhammad Nur; Sufitriyono Sufitriyono (Universitas Negeri Makassar, 2020)
This study investigated the effectiveness of implementation of distributed practice learning model by audio visual media to improve the results of learning basic techniques of badminton through. This research was a experimental methods one group Pretest-posttest design. The research object is students a 4th semester in grade 2018, amounting to 40 people obtained through purposive sampling techniques. Samples were given treatment for 8 times the meeting, in a week 3 times meeting. Data collection techniques of badminton skills test in the form of Wall Volley test, short service, long service and clear test. Data analysis techniques using T-test. The results of this study were a significant effects on the implementation of the distributed practice learning model using audio visual media to improve the basic technical skills of badminton students. The audio-visual media in the application of distributed practice learning models is very effective in improving the learning outcomes of badminton basic engineering skills. Besides being able to facilitate students in understanding the movements learned, also facilitate teachers in delivering learning materials taught at the time, because students can evaluate the movement directly to be perfect through video observation.